Laser surface processing technology for performance enhancement of TENG - Jia Tian; Yue He; Fangpei Li; Wenbo Peng; Yongning He (AIMS Materials Science)
The triboelectric nanogenerator (TENG), as a new energy harvesting device, can efficiently harvest mechanical energy from the environment to provide continuous power for electronic devices, which has great potential for powering intelligent distributed network. Laser processing technology, which enables structural, phase, and property control at different scales, can quickly and easily complete the surface patterning of TENG and facilitate efficient energy harvesting. In this work, we outline the working modes and principles of TENG, review the research progress of laser surface processing technology for fabricating TENG in recent years, including laser-induced graphene (LIG), laser ablation, laser carbonization, laser-induced copper, etc., and perspectives on the challenges and future directions for development of laser surface processing for performance enhancement of TENG.